Prevalence of hypertension in children after early repair of coarctation of the aorta: a cohort study using casual and 24 hour blood pressure measurement. Issue 2 (1st August 2002) - O'Sullivan, J J; Derrick, G; Darnell, R
Abstract : Objective: To study the prevalence of hypertension in a cohort of patients using the current strategy of repair in early childhood. Patients: The cohort of patients with coarctation of the aorta born between 1983 and 1992. Intervention: Casual (mean of three resting readings) and 24 hour blood pressure were measured in 119 children and compared with data from 1034 normal controls. The arch repair and left ventricular parameters were assessed using Doppler echocardiography. Results: Median ages at first intervention and at blood pressure measurement were 0.2 years (interquartile range 0.04–2.0) and 12.0 years (9.0–14.5), respectively. Doppler velocity in the descending aorta was significantly associated with blood pressure ( r = 0.28, p = 0.002 for casual systolic blood pressure (SBP); r = 0.26, p = 0.005 for mean 24 hour SBP). Patients were classified as having "no" (n = 70) or "mild" (n = 49) arch obstruction. Casual SBP was > 95th centile in 28% (34 of 119) overall and in 21% (15 of 70) of the no arch obstruction group. Mean 24 hour SBP was > 95th centile in 30% (36 of 119) overall and in 19% (13 of 70) of the no obstruction group. The sensitivity and specificity of casual SBP in detecting increased 24 hour SBP were 66% and 88%, respectively. Conclusions: This unique study of a large cohort of patients treated for coarctation in early childhood showed that a disappointingly high prevalence of hypertension is already apparent in children aged 7–16 years in the absence of significant arch obstruction, whether assessed by 24 hour or by casual blood pressure measurement.